Chronic pleural empyema – a clinical case-report - Rosário, Lina; Bugalho, António; Santos Matos, Lurdes; Salazar de Sousa, Luis; Sousa Guerreiro, António; da Silva, Menezes; Nunes, José Luís; Caldeira, João; Pinto Marques, António; Otero, Dolores (Portuguese Journal Internal Medicine, 2002)
A 57-year-old male patient was observed in Pulido Valente’s Hospital Rapid Diagnostic Oncology Clinic, in 1999, with complaints of intermittent dysphagia, foetid halitosis and thoracic pain. He had a history of pleuropulmonary tuberculosis when he was 12-years-old, from which chest wall sequelae resulted and he had multiple hospital admissions with pulmonary infections. He was admitted for study, and chest x-rays (CXR) showed the presence of chest-wall lesions and a right pleural effusion. Laboratory analysis of the pleural aspirate revealed an empyema. Upper digestive endoscopy showed a fistula, with drainage of purulent liquid. CXR and thoracic CT scan with oral contrast documented the passage of contrast from the oesophagus into the pleural space, confirming the existence of a oesophago-pleural fistula. The patient underwent oesophageal exclusion surgery, with drainage and decortication of the right pleural space. Two months later oesophagectomy and gastric tube reconstruction was performed. Two years after surgery a relapse of the empyema occurred, and thoracoplasty was necessary. To date there have been no subsequent problems.